GAMBARAN KEPUASAN KELUARGA PASIEN STROKE PADA PEMENUHAN PERSONAL HYGIENE OLEH PERAWAT DI RUANG MAWAR RUMAH SAKIT UMUM DAERAH KABUPATEN CIAMIS TAHUN 2018 - DIta Permatasari; Siti Rohimah; Romlah Romlah (Jurnal Keperawatan Galuh, 2019)
Background Family and patient satisfaction is the first indicator of a hospital's standard and is a measure of service quality. Meeting basic needs is an important action that nurses must take to hospitalized clients, including those in stroke clients. Personal hygiene action is one of the basic needs that nurses must do to clients. Personal hygiene is an action to maintain one's hygiene and health for physical and psychological well-being. The purpose of this study was to describe the family satisfaction of stroke patients in the fulfillment of personal hygiene by nurses in the Rose Room of the Ciamis District General Hospital in 2018. This type of research uses descriptive, namely a research method with the main purpose of making a description or description of an object. The population in this study were all families of stroke patients who were undergoing treatment in the Rose Room of the Ciamis District General Hospital in December 2018 as many as 30 people. Sampling in this study used a total sampling technique, namely the entire population as a sample of the study as many as 30 families of stroke patients. The results showed that the family satisfaction of stroke patients in fulfilling personal hygiene by nurses in the Rose Room of the Ciamis District General Hospital, the highest frequency was quite satisfied category of 11 people (36.7%), satisfied categories were 8 people (26.7%) ), the category of dissatisfaction was 7 people (23.3%) and the lowest frequency was in the very satisfied category of 4 people (13.3%). Suggestions are expected that in nursing services nursing staff should be active in getting new information and knowledge about nursing science, especially regarding the fulfillment of personal hygiene, more intensively conducting socialization and health education about personal hygiene so as to reduce the risk of complications which can ultimately increase their role as professional nurses and satisfaction with family and patients.